1997
DOI: 10.1002/(sici)1096-8644(199708)103:4<471::aid-ajpa5>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the human pelvis: A comparison of direct and radiographic techniques using a modern United States–based sample

Abstract: Seven measurements were taken on a sample of 50 human cadaveric pelves, all white Texans born in the 20th century. Two separate methodologies were used to obtain these data: radiographs and direct measurements. These two methodologies were compared and contrasted, with the relative advantages and disadvantages of each explored. Results indicate that significant differences exist between the two methodologies. Pelvic height, breadth of symphysis, sacro-iliac breadth (P = 0.0001) and anterior upper spinal breadt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…The 99% prediction intervals for the population cover all the pelvic width and height measurements published and so would appear to be an accurate representation of the expected population (Table ). This study matches well with Schroder et al (). There are no clear reasons for the slightly lower mean values in the Seidel et al () study; however, no BMI information was available for comparison, and our subject age range included younger subjects.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The 99% prediction intervals for the population cover all the pelvic width and height measurements published and so would appear to be an accurate representation of the expected population (Table ). This study matches well with Schroder et al (). There are no clear reasons for the slightly lower mean values in the Seidel et al () study; however, no BMI information was available for comparison, and our subject age range included younger subjects.…”
Section: Discussionsupporting
confidence: 94%
“…Schroder et al () reported image‐based (plain radiographic) and direct cadaveric measurements of the same 50 pelves. They found, as did this study, a lower mean pelvic width for the image‐based measurements, despite taking steps to minimize inaccuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few researchers in the past 100 years have employed direct clinical pelvic metric analyses that align with obstetrically significant measures to assess skeletal pelvic samples (Young and Ince, 1940;Heyns, 1944;Segebarth-Orban, 1980;Holland et al, 1982;Iscan and Cotton, 1985;Abitbol, 1987;Tague and Lovejoy, 1986;Tague, 1989;Sibley et al, 1992;Schroeder et al, 1997;Stone, 2000;Kurki, 2007;Okoseimiema and Udoaka, 2013). A few researchers in the past 100 years have employed direct clinical pelvic metric analyses that align with obstetrically significant measures to assess skeletal pelvic samples (Young and Ince, 1940;Heyns, 1944;Segebarth-Orban, 1980;Holland et al, 1982;Iscan and Cotton, 1985;Abitbol, 1987;Tague and Lovejoy, 1986;Tague, 1989;Sibley et al, 1992;Schroeder et al, 1997;Stone, 2000;Kurki, 2007;Okoseimiema and Udoaka, 2013).…”
Section: Measuring Obstetrical Risk In the Pastmentioning
confidence: 99%
“…Terry conducted experiments using cadavers and living subjects to ensure that the tables allowed for the measurement of living stature data from the cadaver. As a result of Terry's standardized protocol, various methodological problems associated with measuring dry versus wet bone, measuring bones from radiographs or reclined cadaveric length are avoided [15][16][17][18]. Unlike other sources of stature data, such as the Forensic Anthropology Databank or FDB [8], reduced measurement error is an added benefit of using the Terry Collection data.…”
Section: Methodsmentioning
confidence: 99%